Disruption Faces, Inequality, and Its Appearance in Religion: An Integrated Paradigm - Syukron Jazila (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
Since the industrial revolution in England around the 18thcentury, the world changed in very fast motion. Sequentially steam engine was found, printing machines, computers, and finally the internet network—a forerunner of the digital era. These all affect without exception, including Indonesia. We live in a world connected one another through communication technology. Departing from this issue, this study focused on the face of religious thought, educational patterns, and culture—especially in Muslims society. Trying to integrate William F. Ogburn's Cultural Lag theory and Disruptive Innovation of Clayton Cristensen, this study found the symptom connection between them. Civilization which consists of two elements: material (technology) and non-material (culture; education) are clearly separated by the abyss. One element flies very fast, and the other crawls slowly. These two things ultimately influence the Muslim religious thinking today. Overlapping the information in digital media every day made religious people did not have time to digest or analyze it. In fact, we found unilateral truth claims from certain groups—in the name of a complete understanding of religion, which is deeply turned out to be ahistorical. Here; disruption is caused by the movement of information that coming so fast—unstoppable and created a shallow, instant and hasty knowledge.